Pengaruh Pelaksanaan Analisis Jabatan Terhadap Peningkatan Profesionalisme Aparatur Negara pada Dinas Pendidikan Kabupaten Ciamis - Nuraeni Hasan; Apri Budianto (Profit: Jurnal Manajemen, Bisnis dan Akuntansi, 2024)
This research is motivated by several problems, including the lack of professionalism of state apparatus which is suspected to be due to the less than optimal implementation of job analysis. This study aims to determine the effect of job analysis implementation on improving the professionalism of state apparatus at the Ciamis Regency Education Office. This study used a descriptive method with a quantitative approach. The respondents in this study were 122 employees of the Ciamis Regency Education Office, so the author took samples using the simple random sampling technique so that the number of samples in this study was 55 people. Analysis was carried out on the data collected from observations, interviews, and questionnaires. The data analysis stage began with validity tests, reliability, ordinal value transformation to intervals, and data analysis using verification/quantitative methods. The results of the study showed that: 1) The implementation of job analysis at the Ciamis Regency Education Office was included in the good category, although there were still indicators that needed to be improved, such as the need to compile job specifications so that it could facilitate determining employees to occupy a position, in addition to the need to continuously improve the results of job analysis so that organizational goals could be achieved as expected. 2) The professionalism of the State Apparatus at the Ciamis Regency Education Office is included in the good category, although there are still several indicators that need to be improved, such as the less than optimal improvement of the ability of government apparatus in anticipating various problems, the ability of apparatus to respond quickly to each problem is still lacking so that the problems faced by employees cannot be resolved quickly. 3) The implementation of job analysis has an effect on increasing the professionalism of the State Apparatus at the Ciamis Regency Education Office. This means that the higher the job analysis carried out on state civil servants, the more the professionalism of state civil servants will increase.